Dental filling kit

By using a specific formula of self-adhesive tooth combination resin and glass ionic cement in the tooth filling kit, the problem of insufficient opening sealing and adhesion in clinical applications is solved, and strong adhesion and good ion release performance are achieved.

JP7667693B2Active Publication Date: 2025-04-23KURARAY NORITAKE DENTAL
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021079276
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-07
Publication Date
2025-04-23
Estimated Expiration
2041-05-07

AI Technical Summary

Technical Problem

In actual clinical applications, existing dental filling kits have problems such as opening sealing and insufficient tooth adhesion. Especially after using a combined resin with a high acid base content, insufficient photocuring depth and poor adhesion of glass ionic cement.

Method used

A specific self-adhesive tooth combination resin and glass ionic cement combination kit is used, where the self-adhesive tooth combination resin contains units with an acid-based content of 1-30% and an acid-free unit, and is equipped with a photocuring initiator, while glass ionic cement contains fluoroaluminosilicate glass powder, polyhydroxy acid-based polymer and water.

Benefits of technology

It realizes efficient sealing and strong adhesion of the dental hole, simplifies the operation steps, avoids the need for use of conditioning agents, and has good ion release performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667693000009
    Figure 0007667693000009
  • Figure 0007667693000010
    Figure 0007667693000010
  • Figure 0007667693000001
    Figure 0007667693000001
Patent Text Reader

Abstract

To provide a dental filling kit that demonstrates excellent cavity sealability and dentin bondability by a simple method of filling a cavity with a self-adhesive dental composite resin and then filling its top with glass ionomer cement.SOLUTION: A dental filling kit contains: a self-adhesive dental composite resin (X) that contains an acidic group-containing monomer (a), an acidic group-free monomer (b), and a photopolymerization initiator (c); and a glass ionomer cement (Y) that contains fluoroaluminosilicate glass powder (f), a polycarboxylic acid polymer (g), and water (h). The content of the acidic group-containing monomer (a) is 1-30 pts.mass relative to 100 pts.mass of the total monomer content of the (a) self-adhesive dental composite resin (X).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a dental filling kit. More specifically, the dental filling kit of the present invention relates to a dental filling kit that can easily achieve both excellent cavity sealing properties and adhesive strength to tooth structure by filling a cavity with a self-adhesive dental composite resin and then filling the upper part with glass ionomer cement. [Background technology]

[0002] To repair tooth tissue (enamel, dentin, and cementum) damaged by caries or other conditions, filling and restorative materials such as filling composite resins and filling compomers, and crown and crown restorative materials such as metal alloys, porcelains, and resin materials are typically used. However, filling and restorative materials and crown and crown restorative materials (collectively referred to herein as "dental restorative materials") generally do not adhere to tooth tissue. For this reason, various adhesive systems using adhesives have traditionally been used to bond tooth tissue and dental restorative materials. A commonly used adhesive system is the so-called acid-etching (total-etching) adhesive system, in which the surface of the tooth is etched using an acid etching agent such as an aqueous phosphoric acid solution, followed by application of a bonding agent to bond the tooth tissue and dental restorative material.

[0003] On the other hand, there are so-called self-etching adhesive systems that do not use acid-etching agents. Traditionally, these systems have been primarily two-step adhesive systems in which a self-etching primer containing an acidic monomer, a hydrophilic monomer, and water is applied to the tooth surface, followed by a bonding agent containing a cross-linking monomer and a polymerization initiator without rinsing with water. However, recently, one-step adhesive systems using one-component dental adhesives (one-component bonding agents) that combine the functions of both a self-etching primer and a bonding agent have become more common. One-component bonding agents generally contain monomer components such as an acidic monomer, a hydrophilic monomer, and a cross-linking monomer, and are typically used with water or a hydrophilic, volatile organic solvent.

[0004] Recently, self-adhesive dental composite resins, which are dental composite resins with adhesive properties, have been developed, and compositions that eliminate the use of bonding agents and reduce the number of operational steps in restorative treatment have begun to be put into practical use (Patent Documents 1 to 3). Furthermore, dental restorative material kits have also been proposed, as in Patent Documents 4 and 5. Generally, bonding agents differ from dental composite resins (such as self-adhesive dental composite resins) in that they contain a solvent (water, organic solvent, etc.) and in the amount of filler they contain. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2004-529946 [Patent Document 2] Japanese Patent Application Publication No. 2017-105716 [Patent Document 3] Japanese Patent Application Publication No. 2018-065831 [Patent Document 4] Japanese Patent Application Laid-Open No. 2006-131621 [Patent Document 5] International Publication No. 2020 / 195026 Summary of the Invention [Problem to be solved by the invention]

[0006] However, according to the inventor's investigations, cavity sealing tests based on actual clinical practice have revealed that the self-adhesive dental materials and self-adhesive dental composite resins described in Patent Documents 1 to 3 have issues with cavity sealing ability.

[0007] Furthermore, for example, Patent Document 4 proposes a dental filling kit in which a bonding material is applied, and then a dental composite resin containing an acidic group-containing monomer is used and light is irradiated all at once, and Patent Document 5 proposes a dental restorative material set in which glass ionomer cement is applied to a predetermined area of ​​a tooth, the applied glass ionomer cement is hardened, and a composite resin containing a (meth)acrylate having an acid group is applied to the predetermined area of ​​the tooth where the glass ionomer cement has hardened.

[0008] However, with the method of Patent Document 4, for example, it was found that the depth of cure was small when using a shade with low transparency, resulting in reduced curing of the bonding material and reduced cavity sealing. Furthermore, with the method of Patent Document 5, the adhesive strength of the glass ionomer cement to tooth tissue was lower than that of a dental composite resin containing a (meth)acrylate with an acidic group, resulting in insufficient cavity sealing. Furthermore, the need for the combined use of a conditioner made the procedure cumbersome. Furthermore, in Patent Document 5, in order to solve the problem of reduced adhesiveness of the cured glass ionomer cement to the cured composite resin, it was considered necessary to apply the glass ionomer cement to the cavity bottom side of the tooth tissue and then apply the dental composite resin on top, taking into account the depth of cure due to the transparency of the dental composite resin (see Patent Document 5, Figures 1 to 3).

[0009] The present invention aims to provide a dental filling kit that uses a simple method to provide excellent cavity sealing properties and adhesive strength to tooth structure by filling the cavity with a self-adhesive dental composite resin and then filling the upper part with glass ionomer cement. [Means for solving the problem]

[0010] After extensive research, the inventors discovered that a dental filling kit comprising a self-adhesive dental composite resin of a specific composition and a glass ionomer cement of a specific composition can solve the above-mentioned problems, and after further research, they completed the present invention.

[0011] That is, the present invention includes the following inventions. [1] A self-adhesive dental composite resin (X) containing a monomer (a) having an acidic group, a monomer (b) not having an acidic group, and a photopolymerization initiator (c); a glass ionomer cement (Y) containing fluoroaluminosilicate glass powder (f), a polycarboxylic acid polymer (g), and water (h); A dental filling kit, wherein the content of the monomer (a) having an acidic group is 1 to 30 parts by mass per 100 parts by mass of the total amount of the monomers in the self-adhesive dental composite resin (X). [2] The dental filling kit described in [1], wherein the self-adhesive dental composite resin (X) further contains a filler (d), and the content of the filler (d) is 50 to 90 parts by mass per 100 parts by mass of the total amount of the self-adhesive dental composite resin (X). [3] A dental filling kit as described in [2], wherein the filler (d) includes a filler (d-ii) having an average particle size of 0.1 μm or more and 1 μm or less and / or a filler (d-iii) having an average particle size of more than 1 μm and 10 μm or less. [4] A dental filling kit according to [3], wherein the filler (d-ii) and / or the filler (d-iii) comprises an inorganic filler containing silicon atoms and / or an inorganic filler composed of an oxide of silicon atoms, the inorganic filler having hydroxyl groups on its surface, and the hydroxyl groups being surface-treated with a surface treatment agent. [5] A dental filling kit according to any one of [2] to [4], wherein the filler (d) comprises at least one combination selected from the group consisting of a combination (I) of a filler (di) having an average particle size of 1 nm or more and less than 0.1 μm and a filler (d-ii) having an average particle size of 0.1 μm or more and 1 μm or less, a combination (II) of a filler (di) having an average particle size of 1 nm or more and less than 0.1 μm and a filler (d-iii) having an average particle size of more than 1 μm and 10 μm or less, a combination (III) of a filler (di) having an average particle size of 1 nm or more and less than 0.1 μm and a filler (d-ii) having an average particle size of more than 1 μm and 10 μm or less, and a combination (IV) of fillers (d-ii) having an average particle size of 0.1 μm or more and 1 μm or less. [6] The dental filling kit according to any one of [1] to [5], wherein the glass ionomer cement (Y) further contains a monomer (i) and a photopolymerization initiator (j). [7] The dental filling kit according to any one of [1] to [6], wherein the self-adhesive dental composite resin (X) is of a one-component type. [8] A dental filling kit according to any one of [1] to [7], wherein the content of the fluoroaluminosilicate glass powder (f) is 25 to 85 parts by mass per 100 parts by mass of the total amount of the glass ionomer cement (Y). [9] A dental filling kit described in any of [1] to [8], wherein the self-adhesive dental composite resin (X) is for direct sealing of the entire cavity or part of it, and the glass ionomer cement (Y) is for covering the surface to which the self-adhesive dental composite resin (X) is applied.

[10] A method for treating a tooth, comprising the steps of applying a self-adhesive dental composite resin (X) to a predetermined area of ​​the tooth, and applying a glass ionomer cement (Y) to the predetermined area to which the self-adhesive dental composite resin (X) has been applied; The self-adhesive dental composite resin (X) comprises a monomer (a) having an acidic group, a monomer (b) not having an acidic group, and a photopolymerization initiator (c), A method for restoring a tooth, wherein the glass ionomer cement (Y) comprises a fluoroaluminosilicate glass powder (f), a polycarboxylic acid polymer (g), and water (h). [Effects of the Invention]

[0012] According to the present invention, a dental filling kit can be provided that, by filling a cavity with a self-adhesive dental composite resin and then filling the upper part with glass ionomer cement, exhibits excellent cavity sealing properties and adhesive strength to tooth substance using a simple method. Furthermore, according to the present invention, a dental filling kit with excellent ion release properties can be provided. Furthermore, according to the present invention, a dental filling kit that is easy to use and has excellent operability, without requiring steps such as the use of a conditioner or bonding material, can be provided. [Brief explanation of the drawings]

[0013] [Figure 1] FIG. 2 is a cross-sectional view showing an example of filling using the dental filling kit of the present invention. [Figure 2] FIG. 2 is a cross-sectional view showing an example of filling using the dental filling kit of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0014] The dental filling kit of the present invention comprises a self-adhesive dental composite resin (X) and a glass ionomer cement (Y). The self-adhesive dental composite resin (X) contains a monomer (a) having an acidic group, a monomer (b) not having an acidic group, and a photopolymerization initiator (c). The content of the monomer (a) having an acidic group in the self-adhesive dental composite resin (X) is 1 to 30 parts by mass per 100 parts by mass of the total amount of the monomers in the self-adhesive dental composite resin (X). The glass ionomer cement (Y) contains a fluoroaluminosilicate glass powder (f), a polycarboxylic acid polymer (g), and water (h).

[0015] In this specification, "(meth)acrylic" is a general term for methacrylic and acrylic, and the same applies to similar expressions (such as "(meth)acrylic acid" and "(meth)acrylonitrile"). In this specification, the upper and lower limits of numerical ranges (such as the content of each component, values ​​calculated from each component, and physical properties) can be combined as appropriate.

[0016] The reason why the dental filling kit of the present invention exhibits excellent cavity sealing properties with a simple method is unclear, but is presumed to be as follows. Specifically, it is believed that simply bonding the composite resin to the tooth structure (e.g., only the enamel) may not be sufficient to achieve excellent cavity sealing properties when filling a cavity with glass ionomer cement (Y). The self-adhesive dental composite resin (X) included in the dental filling kit of the present invention also exhibits excellent adhesion to tooth structure (especially dentin). Therefore, it is believed that the presence of the self-adhesive dental composite resin (X) between the glass ionomer cement (Y) and the tooth structure allows the cavity to be sealed not only at the margins but also at the sides and cavity bottom with the self-adhesive dental composite resin (X). Furthermore, ion release is expected due to the exposed portions of the glass ionomer cement on the cavity surface.

[0017] Each component used in the dental filling kit of the present invention will be described below.

[0018] First, the self-adhesive dental composite resin (X) will be described.

[0019] <Monomer> The monomer used in the self-adhesive dental composite resin (X) of the present invention is preferably a radical monomer. Specific examples of radical monomers include (meth)acrylate monomers, (meth)acrylamide monomers, esters of α-cyanoacrylic acid, (meth)acrylic acid, α-halogenated acrylic acid, crotonic acid, cinnamic acid, sorbic acid, maleic acid, itaconic acid, etc., vinyl esters, vinyl ethers, mono-N-vinyl derivatives, and styrene derivatives. Among these, (meth)acrylate monomers and (meth)acrylamide monomers are preferred from the viewpoint of curing properties. Furthermore, from the viewpoints of adhesion to tooth structure and elastic modulus, the monomer in the self-adhesive dental composite resin (X) of the present invention must contain a monomer (a) having an acidic group and a monomer (b) not having an acidic group.

[0020] <Monomer (a) Having an Acidic Group> The monomer (a) having an acidic group used in the present invention includes, for example, a monomer having at least one acidic group such as a phosphoric acid group, a pyrophosphate group, a thiophosphate group, a phosphonic acid group, a carboxylic acid group, or a sulfonic acid group. The monomer (a) having an acidic group can be used alone or in appropriate combination of two or more. Specific examples of the monomer (a) having an acidic group are shown below.

[0021] Examples of the monomer having a phosphate group include 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyethyl dihydrogen phosphate, 9-(meth)acryloyloxypropyl dihydrogen phosphate, 10-(meth)acryloyloxybutyl dihydrogen phosphate, 11-(meth)acryloyloxybutyl dihydrogen phosphate, 12-(meth)acryloyloxybutyl dihydrogen phosphate, 13-(meth)acryloyloxybutyl dihydrogen phosphate, 14-(meth)acryloyloxybutyl dihydrogen phosphate, 15-(meth)acryloyloxypentyl dihydrogen phosphate, 16-(meth)acryloyloxyhexyl dihydrogen phosphate, 17-(meth)acryloyloxyheptyl dihydrogen phosphate, 18-(meth)acryloyloxybutyl dihydrogen phosphate, 19-(meth)acryloyloxybutyl dihydrogen phosphate, 20-(meth)acryloyloxybutyl dihydrogen phosphate, 21-(meth)acryloyloxybutyl dihydrogen phosphate, 22-(meth)acryloyloxybutyl dihydrogen phosphate, 23-(meth)acryloyloxybutyl dihydrogen phosphate, 24-(meth)acryloyloxybutyl dihydrogen phosphate, 25-(meth)acryloyloxybutyl dihydrogen phosphate, 26-(meth)acryloyloxyhexyl dihydrogen phosphate, 27-(meth)acryloyloxyhexyl dihydrogen phosphate, 28-( Acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyicosyl dihydrogen phosphate phosphate, bis[2-(meth)acryloyloxyethyl]hydrogenphosphate, bis[4-(meth)acryloyloxybutyl]hydrogenphosphate, bis[6-(meth)acryloyloxyhexyl]hydrogenphosphate, bis[8-(meth)acryloyloxyoctyl]hydrogenphosphate, bis[9-(meth)acryloyloxynonyl]hydrogenphosphate, bis[10-(meth)acryloyloxydecyl]hydrogenphosphate, 1,3 2-(meth)acryloyloxypropyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 2-(meth)acryloyloxyethyl-(2-bromoethyl)hydrogen phosphate, 2-methacryloyloxyethyl-(4-methoxyphenyl)hydrogen phosphate, 2-methacryloyloxypropyl-(4-methoxyphenyl)hydrogen phosphate, and acid chlorides, alkali metal salts, and amine salts thereof.

[0022] Examples of monomers having a pyrophosphate group include bis[2-(meth)acryloyloxyethyl] pyrophosphate, bis[4-(meth)acryloyloxybutyl] pyrophosphate, bis[6-(meth)acryloyloxyhexyl] pyrophosphate, bis[8-(meth)acryloyloxyoctyl] pyrophosphate, bis[10-(meth)acryloyloxydecyl] pyrophosphate, and acid chlorides, alkali metal salts, and amine salts thereof.

[0023] Examples of the monomer having a thiophosphate group include 2-(meth)acryloyloxyethyl dihydrogenthiophosphate, 3-(meth)acryloyloxypropyl dihydrogenthiophosphate, 4-(meth)acryloyloxybutyl dihydrogenthiophosphate, 5-(meth)acryloyloxypentyl dihydrogenthiophosphate, 6-(meth)acryloyloxyhexyl dihydrogenthiophosphate, 7-(meth)acryloyloxyheptyl dihydrogenthiophosphate, and 8-(meth)acryloyloxyoctyl dihydrogenthiophosphate. Examples of the acryloyloxypropyl methyl phosphate include acryloyloxypropyl methyl phosphate, 9-(meth)acryloyloxynonyl dihydrogen thiophosphate, 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate, 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate, 20-(meth)acryloyloxyicosyl dihydrogen thiophosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.

[0024] Examples of the monomer having a phosphonic acid group include 2-(meth)acryloyloxyethyl phenylphosphonate, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 10-(meth)acryloyloxydecyl-3-phosphonoacetate, and acid chlorides, alkali metal salts, and ammonium salts thereof.

[0025] Examples of the monomer having a carboxylic acid group include a monofunctional (meth)acrylic acid ester having one carboxyl group or its acid anhydride group in the molecule, and a monofunctional (meth)acrylic acid ester having multiple carboxyl groups or their acid anhydride groups in the molecule.

[0026] Examples of monofunctional monomers having one carboxyl group or an acid anhydride group thereof in the molecule include (meth)acrylic acid, N-(meth)acryloylglycine, N-(meth)acryloylaspartic acid, 2-(meth)acryloyloxyethyl hydrogen succinate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxyethyl hydrogen maleate, O-(meth)acryloyltyrosine, N-(meth)acryloyltyrosine Examples of the acryloyloxybenzoic acid include N-(meth)acryloylphenylalanine, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-o-aminobenzoic acid, 2-(meth)acryloyloxybenzoic acid, 3-(meth)acryloyloxybenzoic acid, 4-(meth)acryloyloxybenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, and N-(meth)acryloyl-4-aminosalicylic acid, as well as compounds in which the carboxyl group of these compounds has been converted to an acid anhydride group.

[0027] Examples of monofunctional monomers having a plurality of carboxyl groups or acid anhydride groups thereof in the molecule include 6-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 9-(meth)acryloyloxynonane-1,1-dicarboxylic acid, 10-(meth)acryloyloxydecane-1,1-dicarboxylic acid, 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid, 12-(meth)acryloyloxydodecane-1,1-dicarboxylic acid, 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyethyl trimellitate, 4-(meth)acryloyloxyethyl trimellitate anhydride ... Examples of suitable acrylic anhydrides include 2-(meth)acryloyloxyethyl-3'-(meth)acryloyloxy-2'-(3,4-dicarboxybenzoyloxy)propyl succinate, 6-(meth)acryloyloxyethyl naphthalene-1,2,6-tricarboxylic anhydride, 6-(meth)acryloyloxyethyl naphthalene-2,3,6-tricarboxylic anhydride, 4-(meth)acryloyloxyethyl carbonylpropionoyl-1,8-naphthalic anhydride, and 4-(meth)acryloyloxyethyl naphthalene-1,8-tricarboxylic anhydride.

[0028] Examples of the monomer having a sulfonic acid group include 2-sulfoethyl (meth)acrylate.

[0029] Among the above-mentioned monomers (a) having an acidic group, from the viewpoint of achieving good adhesive strength when used as a self-adhesive dental composite resin (X), it is preferable to contain a monomer having a phosphate group or a monomer having a carboxylic acid group, and examples thereof include 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyl Oxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyicosyl dihydrogen phosphate, 4-(meth)acryloyloxyethyl trimellitate anhydride, 4-(meth)acryloyloxyethyl trimellitate, 11-(meth)acryloyloxyundecane-1,1-Dicarboxylic acid and a mixture of 2-methacryloyloxyethyl dihydrogen phosphate and bis(2-methacryloyloxyethyl)hydrogen phosphate are more preferred, and 8-(meth)acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, and 20-(meth)acryloyloxyicosyl dihydrogen phosphate are even more preferred, with 10-(meth)acryloyloxydecyl dihydrogen phosphate being the most preferred from the viewpoint of a balance of curability.

[0030] In order to achieve the effects of the present invention, it is particularly important that the content of the acidic group-containing monomer (a) in the self-adhesive dental composite resin (X) of the present invention be determined relative to the total amount of monomers. From the viewpoint of achieving both adhesion to the glass ionomer cement (Y) and adhesion to tooth structure (particularly dentin), the content of the acidic group-containing monomer (a) must be 1 to 30 parts by mass, preferably 1 to 29 parts by mass, more preferably 2.5 to 27.5 parts by mass, and even more preferably 5 to 25 parts by mass, per 100 parts by mass of the total amount of monomers. If the content of the acidic group-containing monomer (a) exceeds 30 parts by mass, adhesion to dentin decreases.

[0031] <Monomer (b) having no acidic group> Examples of the monomer (b) having no acidic group in the present invention include an asymmetric acrylamide-methacrylate compound (b-1); a hydrophobic monomer (b-2) having no acidic group and having a solubility in water at 25°C of less than 10 g / L (hereinafter simply referred to as "hydrophobic monomer (b-2)"); and a hydrophilic monomer (b-3) having no acidic group and having a solubility in water at 25°C of 10 g / L or more (hereinafter simply referred to as "hydrophilic monomer (b-3)"). The monomer (b) having no acidic group may be used alone or in combination of two or more. In the present invention, compounds that do not have an acidic group and contain an acrylamide group and a methacryloyloxy group are defined as asymmetric acrylamide-methacrylate compounds (b-1), and compounds that do not have an acidic group and are not included in the asymmetric acrylamide-methacrylate compounds (b-1) are classified into hydrophobic monomers (b-2) and hydrophilic monomers (b-3) according to the degree of hydrophilicity.

[0032] Asymmetric acrylamide-methacrylate compound (b-1) A preferred embodiment of the present invention is a dental filling kit including a self-adhesive dental composite resin (X) containing an asymmetric acrylamide-methacrylate ester compound (b-1). The asymmetric acrylamide-methacrylate ester compound (b-1) is preferably a compound represented by the following general formula (1), since it improves the adhesion of the self-adhesive dental composite resin (X) to tooth structure.

[0033] [ka] In the formula, Z represents a C1 to C8 linear or branched aliphatic or aromatic group which may have a substituent, and the aliphatic group is -O-, -S-, -CO-, -CO-O-, -O-CO-, -NR 1 -, -CO-NR 1 -, -NR 1 -CO-, -CO-O-NR 1 -, -O-CO-NR 1 - and -NR 1 -CO-NR1 - may be interrupted by at least one linking group selected from the group consisting of 1 represents a hydrogen atom or a C1 to C8 linear or branched aliphatic group which may have a substituent.

[0034] Z is a moiety that adjusts the hydrophilicity of the asymmetric acrylamide-methacrylate compound (b-1). The optionally substituted C1-C8 aliphatic group represented by Z may be either a saturated aliphatic group (an alkylene group or a cycloalkylene group (e.g., a 1,4-cyclohexylene group)) or an unsaturated aliphatic group (an alkenylene group or an alkynylene group). From the viewpoints of availability, ease of production, and chemical stability, a saturated aliphatic group (an alkylene group) is preferred. From the viewpoints of adhesion to tooth substrate and polymerization curing properties, Z is preferably a linear or branched C1-C4 aliphatic group that may have a substituent, and more preferably a linear or branched C2-C4 aliphatic group that may have a substituent. The aliphatic group is preferably an alkylene group. Examples of the C1-C8 alkylene group include a methylene group, an ethylene group, an n-propylene group, an isopropylene group, and an n-butylene group.

[0035] Examples of the aromatic group represented by Z, which may have a substituent, include an aryl group and an aromatic heterocyclic group. As the aromatic group, an aryl group is more preferable than an aromatic heterocyclic group. The heterocycle of the aromatic heterocyclic group is generally unsaturated. The aromatic heterocycle is preferably a 5- or 6-membered ring. As an aryl group, a phenyl group is preferable. As an aromatic heterocyclic group, for example, a furan group, a thiophene group, a pyrrole group, an oxazole group, an isoxazole group, a thiazole group, an isothiazole group, an imidazole group, a pyrazole group, a furazan group, a triazole group, a pyran group, a pyridine group, a pyridazine group, a pyrimidine group, a pyrazine group, and a 1,3,5-triazine group are preferable. Among the aromatic groups, a phenyl group is particularly preferable.

[0036] R 1The aliphatic group in R may be either a saturated aliphatic group (an alkyl group) or an unsaturated aliphatic group (an alkenyl group or an alkynyl group), and is preferably a saturated aliphatic group (an alkyl group) from the viewpoints of availability, ease of production, and chemical stability. 1 Examples of the C1 to C8 linear or branched alkyl group in the formula (I) include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a sec-pentyl group, a neopentyl group, a tert-pentyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1,1-dimethylbutyl group, a 2,2-dimethylbutyl group, a 3,3-dimethylbutyl group, and a 2-ethylbutyl group, and preferred are a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, and a tert-butyl group.

[0037] R 1 As the alkyl group, a hydrogen atom or a linear or branched C1 to C4 alkyl group which may have a substituent is more preferred, and a hydrogen atom or a linear or branched C1 to C3 alkyl group which may have a substituent is even more preferred.

[0038] When the aliphatic group of Z is interrupted by the linking group, the number of linking groups is not particularly limited, but may be about 1 to 10, preferably 1, 2, or 3, and more preferably 1 or 2. Furthermore, in the formula (1), the aliphatic group of Z is preferably not interrupted by consecutive linking groups. That is, it is preferable that the linking groups are not adjacent to each other. The linking group is preferably at least one linking group selected from the group consisting of -O-, -S-, -CO-, -CO-O-, -O-CO-, -NH-, -CO-NH-, -NH-CO-, -CO-O-NH-, -O-CO-NH-, and -NH-CO-NH-, and more preferably at least one linking group selected from the group consisting of -O-, -S-, -CO-, -NH-, -CO-NH-, and -NH-CO-.

[0039] Examples of the substituent in Z include a halogen atom (fluorine atom, chlorine atom, bromine atom, iodine atom), a carboxyl group, a C2 to C6 linear or branched acyl group, a C1 to C6 linear or branched alkyl group, and a C1 to C6 linear or branched alkoxy group.

[0040] Specific examples of the asymmetric acrylamide-methacrylate compound (b-1) include, but are not limited to, the following:

[0041] [ka]

[0042] Among these, from the viewpoints of adhesion to tooth tissue and polymerization curing properties, asymmetric acrylamide-methacrylate compounds in which Z is a C2-C4 linear or branched aliphatic group which may have a substituent are preferred, with N-methacryloyloxyethyl acrylamide (commonly known as "MAEA"), N-methacryloyloxypropyl acrylamide, N-methacryloyloxybutyl acrylamide, N-(1-ethyl-(2-methacryloyloxy)ethyl)acrylamide, and N-(2-(2-methacryloyloxyethoxy)ethyl)acrylamide being more preferred, and MAEA and N-methacryloyloxypropyl acrylamide being even more preferred from the viewpoint of high hydrophilicity which is involved in penetration into the collagen layer of dentin.

[0043] The asymmetric acrylamide-methacrylate ester compound (b-1) may be used alone or in combination of two or more. The content of the asymmetric acrylamide-methacrylate ester compound (b-1) is not particularly limited as long as the effects of the present invention are achieved, but is preferably 1 to 60 parts by mass, more preferably 2 to 45 parts by mass, even more preferably 3 to 30 parts by mass, and particularly preferably 5 to 25 parts by mass, per 100 parts by mass of the total amount of monomers in the self-adhesive dental composite resin (X) of the present invention.

[0044] Hydrophobic monomers without acidic groups (b-2) A preferred embodiment is a dental filling kit including a self-adhesive dental composite resin (X) containing a hydrophobic monomer (b-2) that does not have an acidic group. The hydrophobic monomer (b-2) that does not have an acidic group improves the handleability of the self-adhesive dental composite resin (X) and the mechanical strength of the cured product. The hydrophobic monomer (b-2) is preferably a radical monomer that does not have an acidic group but has a polymerizable group. From the viewpoint of ease of radical polymerization, the polymerizable group is preferably a (meth)acrylic group and / or a (meth)acrylamide group. The hydrophobic monomer (b-2) refers to a monomer that does not have an acidic group, does not correspond to the asymmetric acrylamide-methacrylate ester compound (b-1), and has a solubility in water at 25°C of less than 10 g / L. Examples of the hydrophobic monomer (b-2) include crosslinkable monomers such as bifunctional aromatic compound monomers, bifunctional aliphatic compound monomers, and trifunctional or higher functional monomers.

[0045] Examples of aromatic compound-based bifunctional monomers include 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, phenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, and the like. Among these, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (commonly known as "Bis-GMA"), 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (having an average number of moles of ethoxy groups added of 2.6, commonly known as "D-2.6E"), 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, and 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane are preferred.

[0046] Examples of aliphatic compound-based bifunctional monomers include glycerol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, and 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)di(meth)acrylate. Among these, triethylene glycol diacrylate, triethylene glycol dimethacrylate (commonly known as "3G"), neopentyl glycol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (commonly known as "UDMA"), 1,10-decanediol dimethacrylate (commonly known as "DD"), and 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate are preferred.

[0047] Examples of trifunctional or higher functional monomers include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetra(meth)acrylate, and 1,7-diacryloyloxy-2,2,6,6-tetra(meth)acryloyloxymethyl-4-oxaheptane. Among these, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate is preferred.

[0048] Among the hydrophobic monomers (b-2), aromatic bifunctional monomers and aliphatic bifunctional monomers are preferred in terms of mechanical strength and handling. Bis-GMA and D-2.6E are preferred aromatic bifunctional monomers. Glycerol di(meth)acrylate, 3G, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, DD, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, and UDMA are preferred aliphatic bifunctional monomers.

[0049] Among the above hydrophobic monomers (b-2), Bis-GMA, D-2.6E, 3G, UDMA, and DD are more preferred, and D-2.6E, 3G, and Bis-GMA are even more preferred, from the viewpoint of good adhesion to tooth tissue when used as a self-adhesive dental composite resin (X) (composition).

[0050] The hydrophobic monomer (b-2) may be used alone or in combination of two or more. The content of the hydrophobic monomer (b-2) in the self-adhesive dental composite resin (X) of the present invention is preferably 20 to 98 parts by mass, more preferably 40 to 95 parts by mass, and even more preferably 60 to 92 parts by mass, per 100 parts by mass of the total amount of monomers. When the content of the hydrophobic monomer (b-2) is equal to or less than the upper limit described below, it is easy to prevent a decrease in the wettability of the self-adhesive dental composite resin (X) to tooth structure and a decrease in adhesive strength, and when the content is equal to or greater than the lower limit described above, it is easy to obtain the desired mechanical strength of the cured product.

[0051] Hydrophilic monomers without acidic groups (b-3) A preferred embodiment is a dental filling kit including a self-adhesive dental composite resin (X) in which the monomer (b) without an acidic group contains a hydrophilic monomer (b-3) without an acidic group. The hydrophilic monomer (b-3) improves the wettability of the self-adhesive dental composite resin (X) to tooth structure. The hydrophilic monomer (b-3) is preferably a radical monomer without an acidic group and a polymerizable group. From the viewpoint of ease of radical polymerization, the polymerizable group is preferably a (meth)acrylic group and / or a (meth)acrylamide group. The hydrophilic monomer (b-3) refers to a monomer that does not contain an acidic group, does not correspond to the asymmetric acrylamide-methacrylate ester compound (b-1), and has a solubility in water at 25°C of 10 g / L or more. A monomer with a solubility of 30 g / L or more is preferred, and a monomer that is soluble in water at any ratio at 25°C is more preferred. The hydrophilic monomer is preferably one having a hydrophilic group such as a hydroxyl group, an oxymethylene group, an oxyethylene group, an oxypropylene group, an amide group, etc. Examples of the hydrophilic monomer (b-3) include hydrophilic monofunctional (meth)acrylate monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 1,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 2-((meth)acryloyloxy)ethyltrimethylammonium chloride, and polyethylene glycol di(meth)acrylate (having 9 or more oxyethylene groups); monofunctional (meth)acrylamide monomers such as methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N-bis(2-hydroxyethyl) (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, diacetone (meth)acrylamide, 4-(meth)acryloylmorpholine, N-trihydroxymethyl-N-methyl (meth)acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide.

[0052] Among these hydrophilic monomers (b-3), from the viewpoint of adhesion to tooth structure, 2-hydroxyethyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, diacetone (meth)acrylamide, and hydrophilic monofunctional (meth)acrylamide monomers are preferred, and 2-hydroxyethyl (meth)acrylate, N,N-dimethylacrylamide, and N,N-diethylacrylamide are more preferred. One type of hydrophilic monomer (b-3) may be blended alone, or two or more types may be blended in combination.

[0053] The content of the hydrophilic monomer (b-3) in the self-adhesive dental composite resin (X) of the present invention is preferably in the range of 0 to 50 parts by mass, more preferably 0 to 40 parts by mass, and even more preferably 0 to 30 parts by mass, per 100 parts by mass of the total amount of monomers. The content of the hydrophilic monomer (b-3) may be 0 part by mass, per 100 parts by mass of the total amount of monomers. When the content of the hydrophilic monomer (b-3) in the self-adhesive dental composite resin (X) of the present invention is equal to or greater than the lower limit, a sufficient improvement in adhesive strength is likely to be obtained, and when the content is equal to or less than the upper limit, the desired mechanical strength of the cured product is likely to be obtained.

[0054] The content of the monomer (b) without an acidic group in the self-adhesive dental composite resin (X) is preferably 60 to 99 parts by mass, more preferably 65 to 97 parts by mass, and even more preferably 70 to 95 parts by mass, per 100 parts by mass of the total amount of monomers in the self-adhesive dental composite resin (X). From the viewpoint of adhesion to tooth structure, the mass ratio of the hydrophobic monomer (b-2) to the hydrophilic monomer (b-3) ((b-2):(b-3)) is preferably 10:0 to 1:2, more preferably 10:0 to 1:1, and even more preferably 10:0 to 2:1.

[0055] A preferred embodiment includes a self-adhesive dental composite resin (X) that is substantially free of difunctional or higher (meth)acrylamide monomers. Another preferred embodiment includes a self-adhesive dental composite resin (X) that is substantially free of trifunctional or higher (meth)acrylamide monomers. Another preferred embodiment includes a self-adhesive dental composite resin (X) that is substantially free of a hydrogen phosphate diester group-containing monomer. The hydrogen phosphate diester group-containing monomer preferably has a (meth)acryloyloxy group and / or a (meth)acrylamide group. In the present invention, "substantially free of a certain monomer" means that the content of the monomer is less than 0.5 parts by mass, preferably less than 0.1 parts by mass, more preferably less than 0.01 parts by mass, or even 0 parts by mass, per 100 parts by mass of the total amount of monomers contained in the self-adhesive dental composite resin (X). Furthermore, the content of the monomer that is substantially not contained may be less than 0.5% by mass, or may be less than 0.1% by mass, in the entire self-adhesive dental composite resin (X).

[0056] Another preferred embodiment is a self-adhesive dental composite resin (X) that is substantially free of a (meth)acrylic block copolymer. The molecular weight distribution (weight average molecular weight / number average molecular weight) of the (meth)acrylic block copolymer may be, for example, 1.02 to 2.00. The molecular weight distribution can be measured by a known method, for example, gel permeation chromatography (GPC), and calculated as a value converted into standard polystyrene. The (meth)acrylic block copolymer may be difunctional or higher, or tetrafunctional or higher.

[0057] <Photopolymerization initiator (c)> The photopolymerization initiator (c) is classified into a water-soluble photopolymerization initiator (c-1) and a water-insoluble photopolymerization initiator (c-2). As the photopolymerization initiator (c), only the water-soluble photopolymerization initiator (c-1) may be used, only the water-insoluble photopolymerization initiator (c-2) may be used, or the water-insoluble photopolymerization initiator (c-2) and the water-insoluble photopolymerization initiator (c-2) may be used in combination, but it is preferable to use them in combination.

[0058] Water-soluble photopolymerization initiator (c-1) The water-soluble photopolymerization initiator (c-1) improves polymerization curing at the hydrophilic tooth surface interface, achieving high adhesive strength. The water-soluble photopolymerization initiator (c-1) has a solubility in water at 25°C of 10 g / L or more, preferably 15 g / L or more, more preferably 20 g / L or more, and even more preferably 25 g / L or more. A solubility of 10 g / L or more allows the water-soluble photopolymerization initiator (c-1) to dissolve sufficiently in the water in the tooth at the adhesive interface, making it easier to achieve a polymerization-promoting effect.

[0059] Examples of the water-soluble photopolymerization initiator (c-1) include water-soluble thioxanthones, water-soluble acylphosphine oxides, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one in which a (poly)ethylene glycol chain is introduced to the hydroxyl group, 1-hydroxycyclohexyl phenyl ketone in which a (poly)ethylene glycol chain is introduced to the hydroxyl group and / or phenyl group, and 1-hydroxycyclohexyl phenyl ketone in which -OCHCOO is introduced to the phenyl group. - Na + those in which a (poly)ethylene glycol chain has been introduced into the hydroxyl group and / or phenyl group of 2-hydroxy-2-methyl-1-phenylpropan-1-one; those in which -OCH2COO has been introduced into the phenyl group of 2-hydroxy-2-methyl-1-phenylpropan-1-one - Na +and α-aminoalkylphenones such as 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropan-1-one and 2-benzyl-2-(dimethylamino)-1-[(4-morpholino)phenyl]-1-butanone in which the amino group is converted into a quaternary ammonium salt.

[0060] Examples of the water-soluble thioxanthones include 2-hydroxy-3-(9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1-methyl-9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2- Hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(3,4-dimethyl-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, 2-hydroxy-3-(1,3,4-trimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propanaminium chloride, and the like can be used.

[0061] Examples of the water-soluble acylphosphine oxides include acylphosphine oxides represented by the following general formula (2) or (3).

[0062] [ka]

[0063] [ka]

[0064] In formulas (2) and (3), R2 , R 3 , R 4 , R 5 , R 6 , and R 7 are each independently a C1 to C4 linear or branched alkyl group or a halogen atom, and M is a hydrogen ion, an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN + R 9 R 10 R 11 (In the formula, R 9 , R 10 , and R 11 are each independently an organic group or a hydrogen atom), n is 1 or 2, X is a C1-C4 linear or branched alkylene group, and R 8 -CH(CH3)COO(C2H4O) p It is represented by CH3, and p represents an integer of 1 to 1000.

[0065] R 2 , R 3 , R 4 , R 5 , R 6 , and R 7 The alkyl group of R is not particularly limited as long as it is a C1 to C4 linear or branched chain group, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a 2-methylpropyl group, and a tert-butyl group. 2 , R 3 , R 4 , R 5 , R 6 , and R 7 The alkyl group is preferably a C1 to C3 linear alkyl group, more preferably a methyl group or an ethyl group, and even more preferably a methyl group. Examples of X include a methylene group, an ethylene group, an n-propylene group, an isopropylene group, and an n-butylene group. X is preferably a C1 to C3 linear alkylene group, more preferably a methylene group or an ethylene group, and even more preferably a methylene group.

[0066] When M is a pyridinium ion, examples of the substituent on the pyridine ring include a halogen atom (fluorine atom, chlorine atom, bromine atom, iodine atom), a carboxyl group, a C2-C6 linear or branched acyl group, a C1-C6 linear or branched alkyl group, a C1-C6 linear or branched alkoxy group, etc. M is an alkali metal ion, an alkaline earth metal ion, a magnesium ion, a pyridinium ion (the pyridine ring may have a substituent), or HN + R 9 R 10 R 11 (wherein the symbols have the same meanings as above) is preferred. Examples of alkali metal ions include lithium ion, sodium ion, potassium ion, rubidium ion, and cesium ion. Examples of alkaline earth metal ions include calcium ion, strontium ion, barium ion, and radium ion. R 9 , R 10 , and R 11 Examples of the organic group include the same groups as the substituents on the pyridine ring (excluding halogen atoms).

[0067] Among these, R 2 , R 3 , R 4 , R 5 , R 6 , and R 7 In terms of storage stability and color stability in the composition, compounds in which all of the groups are methyl groups are particularly preferred. Furthermore, examples of the ammonium ion include ammonium ions derived from various amines. Examples of amines include ammonia, trimethylamine, diethylamine, dimethylaniline, ethylenediamine, triethanolamine, N,N-dimethylamino methacrylate, 4-(N,N-dimethylamino)benzoic acid and its alkyl esters, 4-(N,N-diethylamino)benzoic acid and its alkyl esters, and N,N-bis(2-hydroxyethyl)-p-toluidine.

[0068] R 8From the viewpoint of adhesiveness, p is preferably 1 or more, more preferably 2 or more, even more preferably 3 or more, particularly preferably 4 or more, and is preferably 1000 or less, more preferably 100 or less, even more preferably 75 or less, particularly preferably 50 or less.

[0069] Among these water-soluble acylphosphine oxides, the water-soluble acylphosphine oxide represented by the general formula (2) n+ is a lithium ion, and 8 A compound represented by the general formula (3) synthesized from polyethylene glycol methyl ether methacrylate having a molecular weight of 950, which corresponds to the group represented by the formula (3), is particularly preferred.

[0070] Water-soluble acylphosphine oxides having such a structure can be synthesized according to known methods, and some are commercially available. For example, they can be synthesized by the methods disclosed in JP-A-57-197289 and WO 2014 / 095724. The water-soluble photopolymerization initiator (c-1) may be used alone or in combination of two or more.

[0071] The water-soluble photopolymerization initiator (c-1) may be dissolved in the self-adhesive dental composite resin (X) or dispersed in the form of a powder.

[0072] When the water-soluble photopolymerization initiator (c-1) is dispersed as a powder, if the average particle size of the powder is too large, it tends to settle, so the average particle size is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. On the other hand, if the average particle size of the powder is too small, the specific surface area of ​​the powder becomes too large, reducing the amount dispersible in the composition, so the average particle size is preferably 0.01 μm or more. That is, the average particle size of the water-soluble photopolymerization initiator (c-1) is preferably in the range of 0.01 to 500 μm, more preferably 0.01 to 100 μm, and even more preferably 0.01 to 50 μm.

[0073] The average particle size of the powder of the water-soluble photopolymerization initiator (c-1) can be calculated as the volume average particle size after performing image analysis using image analysis particle size distribution measurement software (Mac-View; manufactured by Mountec Co., Ltd.) based on electron microscope photographs of 100 or more particles.

[0074] When the water-soluble photopolymerization initiator (c-1) is dispersed as a powder, the shape of the water-soluble photopolymerization initiator (c-1) is not particularly limited, and various shapes such as spherical, needle-like, plate-like, crushed, etc. can be mentioned. The water-soluble photopolymerization initiator (c-1) can be prepared by a conventionally known method such as a pulverization method, a freeze-drying method, or a reprecipitation method. From the viewpoint of the average particle size of the obtained powder, the freeze-drying method and the reprecipitation method are preferred, and the freeze-drying method is more preferred.

[0075] From the viewpoint of the curing property of the self-adhesive dental composite resin (X), the content of the water-soluble photopolymerization initiator (c-1) is preferably 0.01 to 20 parts by mass per 100 parts by mass of the total amount of monomers in the self-adhesive dental composite resin (X). From the viewpoint of adhesive strength to tooth structure, the content is more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass. When the content of the water-soluble photopolymerization initiator (c-1) is equal to or greater than the lower limit, polymerization at the adhesive interface proceeds sufficiently, and sufficient adhesive strength is likely to be obtained. On the other hand, when the content of the water-soluble photopolymerization initiator (c-1) is equal to or less than the upper limit, sufficient adhesive strength is likely to be obtained.

[0076] Non-water-soluble photopolymerization initiator (c-2) From the viewpoint of curing property, the self-adhesive dental composite resin (X) of the present invention preferably contains, in addition to the water-soluble photopolymerization initiator (c-1), a water-insoluble photopolymerization initiator (c-2) (hereinafter, sometimes referred to as the water-insoluble photopolymerization initiator (c-2)) having a solubility in water at 25°C of less than 10 g / L. The water-insoluble photopolymerization initiator (c-2) used in the present invention can be a known water-insoluble photopolymerization initiator. The water-insoluble photopolymerization initiator (c-2) may be used alone or in combination of two or more.

[0077] Examples of the water-insoluble photopolymerization initiator (c-2) include (bis)acylphosphine oxides, thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, and α-aminoketone compounds other than the water-soluble photopolymerization initiator (c-1).

[0078] Among the (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, and benzoyldi(2,6-dimethylphenyl)phosphonate. Examples of bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.

[0079] Examples of the thioxanthones include thioxanthone and 2-chlorothioxanthen-9-one.

[0080] Examples of the ketals include benzyl dimethyl ketal and benzyl diethyl ketal.

[0081] Examples of the α-diketones include diacetyl, benzyl, dl-camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4′-oxybenzyl, acenaphthenequinone, etc. Among these, dl-camphorquinone is particularly preferred because it has a maximum absorption wavelength in the visible light region.

[0082] Examples of the coumarins include 3,3'-carbonylbis(7-diethylaminocoumarin), 3-(4-methoxybenzoyl)coumarin, 3-thienoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromo Coumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl) )coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3-(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzoyl)benzo[f]coumarin, 3-(4-ethoxycinnamoyl)-7-methoxycoumarin, 3-(4-dimethylaminocinnamoyl)coumarin, 3-(4-diphenylaminocinnamoyl)coumarin, 3-[(3-dimethylbenzothiazol-2-ylidene)acetyl]coumarin, 3-[(1-methylnaphtho[1,2-d]thiazol-2-ylidene)acetyl]coumarin, 3,3'-carbo Nylbis(6-methoxycoumarin), 3,3'-carbonylbis(7-acetoxycoumarin), 3,3'-carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylaminocoumarin), 3,Examples of compounds include those described in JP-A-9-3109 and JP-A-10-245525, such as 3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, and 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one.

[0083] Among the above-mentioned coumarins, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly preferred.

[0084] Examples of the anthraquinones include anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1-bromoanthraquinone, 1,2-benzanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, and 1-hydroxyanthraquinone.

[0085] Examples of the benzoin alkyl ether compounds include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.

[0086] Examples of the α-aminoketone compounds include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one.

[0087] Among these water-insoluble photopolymerization initiators (c-2), it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides, α-diketones, and coumarins, which provides a self-adhesive dental composite resin (X) that has excellent photocurability in the visible and near-ultraviolet regions and exhibits sufficient photocurability using any light source, including a halogen lamp, a light-emitting diode (LED), and a xenon lamp.

[0088] The content of the water-insoluble photopolymerization initiator (c-2) is not particularly limited, but from the viewpoint of the curing property of the resulting self-adhesive dental composite resin (X), it is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 7 parts by mass, and even more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the total amount of monomers in the self-adhesive dental composite resin (X) of the present invention. By keeping the content of the water-insoluble photopolymerization initiator (c-2) at or below the upper limit, sufficient bond strength can be easily obtained even when the polymerization performance of the water-insoluble photopolymerization initiator (c-2) itself is low, and further, precipitation of the water-insoluble photopolymerization initiator (c-2) itself from the self-adhesive dental composite resin (X) can be suppressed.

[0089] When a water-soluble photoinitiator (c-1) and a water-insoluble photoinitiator (c-2) are used in combination, the mass ratio of the water-soluble photoinitiator (c-1) to the water-insoluble photoinitiator (c-2) [(c-1):(c-2)] is preferably 10:1 to 1:10, more preferably 7:1 to 1:7, even more preferably 5:1 to 1:5, and particularly preferably 3:1 to 1:3. If the water-soluble photoinitiator (c-1) is contained in a mass ratio of more than 10:1, the curing property of the self-adhesive dental composite resin (X) itself may be reduced, making it difficult to achieve high bond strength. On the other hand, if the water-insoluble photoinitiator (c-2) is contained in a mass ratio of more than 1:10, although the curing property of the self-adhesive dental composite resin (X) itself is enhanced, the polymerization promotion at the adhesive interface may be insufficient, making it difficult to achieve high bond strength.

[0090] <Filler (d)> The self-adhesive dental composite resin (X) of the present invention may contain a filler (d) to adjust handling properties and to increase the mechanical strength of the cured product. Examples of such fillers include inorganic fillers, organic-inorganic composite fillers, and organic fillers. The filler (d) may be used alone or in combination of two or more.

[0091] Examples of inorganic filler materials include inorganic fillers containing silicon atoms and inorganic fillers composed of oxides, such as quartz, silica, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, strontium calcium fluoroaluminosilicate glass, ytterbium oxide, and silica-coated ytterbium fluoride. These may also be used alone or in combination of two or more. Among these, quartz, silica, silica-zirconia, barium glass, ytterbium oxide, and silica-coated ytterbium fluoride are preferred, and quartz, silica, silica-zirconia, barium glass, and silica-coated ytterbium fluoride are more preferred, in terms of the mechanical strength and transparency of the resulting self-adhesive dental composite resin (X). From the standpoint of the handleability and mechanical strength of the resulting self-adhesive dental composite resin (X), the average particle size of the inorganic filler is preferably 0.001 to 50 μm, and more preferably 0.001 to 10 μm. In the present invention, when the inorganic filler is surface-treated as described below, the average particle size of the inorganic filler refers to the average particle size before the surface treatment. A preferred embodiment is a self-adhesive dental composite resin (X) in which the filler (d) is an inorganic filler.

[0092] Another preferred embodiment is a dental filling kit in which the filler (d) of the self-adhesive dental composite resin (X) includes a filler (d-ii) having an average particle size of 0.1 μm to 1 μm (hereinafter, sometimes simply referred to as "filler (d-ii)") and / or a filler (d-iii) having an average particle size of more than 1 μm and not more than 10 μm (hereinafter, sometimes simply referred to as "filler (d-iii)"). When the filler (d) of the self-adhesive dental composite resin (X) includes filler (d-ii) and / or filler (d-iii), superior adhesion to tooth structure and superior cavity sealing properties can be achieved when combined with a predetermined content of the monomer (a) having an acidic group and, if necessary, other components. Another preferred embodiment is a dental filling kit in which the filler (d) of the self-adhesive dental composite resin (X) comprises filler (d-ii) and / or filler (d-iii), and the filler (d-ii) and / or filler (d-iii) comprises an inorganic filler containing silicon atoms or an inorganic filler composed of an oxide, the inorganic filler having hydroxyl groups on its surface, and the hydroxyl groups have been surface-treated with a surface treatment agent. When the self-adhesive dental composite resin (X) contains an inorganic filler surface-treated with a surface treatment agent, superior adhesion to tooth structure and superior cavity sealing properties can be achieved when the self-adhesive dental composite resin (X) is applied to the cavity floor prior to the glass ionomer cement (Y). In any of the preferred embodiments described above, the filler (d) of the self-adhesive dental composite resin (X) is preferably a combination (I) of a filler (di) having an average particle size of 1 nm or more and less than 0.1 μm and a filler (d-ii) having an average particle size of 0.1 μm or more and 1 μm or less, a combination (II) of a filler (di) having an average particle size of 1 nm or more and less than 0.1 μm and a filler (d-iii) having an average particle size of more than 1 μm and 10 μm or less, or a combination (IV) of two fillers (d-ii), with the combinations (I) and (II) being particularly preferred.

[0093] The shape of the inorganic filler is not particularly limited, and the particle size of the filler can be appropriately selected and used. Examples include amorphous fillers and spherical fillers. From the viewpoint of improving the mechanical strength of the cured product of the self-adhesive dental composite resin (X), it is preferable to use a spherical filler as the inorganic filler. Here, the spherical filler is a filler in which, when photographed with an electron microscope, the particles observed within a unit field of view are rounded and have an average uniformity of 0.6 or more, calculated by dividing the particle diameter in a direction perpendicular to the maximum diameter by the maximum diameter. The average particle diameter of the spherical filler is preferably 0.05 to 5 μm. By having an average particle diameter equal to or greater than the lower limit, it is possible to easily obtain a sufficient spherical filler filling rate in the self-adhesive dental composite resin (X), and to easily obtain the desired mechanical strength. On the other hand, by having an average particle diameter equal to or less than the upper limit, it is possible to prevent a decrease in the surface area of ​​the spherical filler, and to easily obtain a cured product of the self-adhesive dental composite resin (X) having the desired mechanical strength.

[0094] The inorganic filler may be surface-treated with a known surface treatment agent such as a silane coupling agent before use, if necessary, to adjust the fluidity of the self-adhesive dental composite resin (X). For example, by surface-treating the hydroxyl groups present on the surface of the inorganic filler with a surface treatment agent, an inorganic filler with surface-treated hydroxyl groups can be obtained. Examples of surface treatment agents include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltrichlorosilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloyloxypropyltrimethoxysilane, 8-methacryloyloxyoctyltrimethoxysilane, 11-methacryloyloxyundecyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.

[0095] The surface treatment method can be any known method, without particular limitation, and includes, for example, spraying the surface treatment agent onto the inorganic filler while vigorously stirring it, dispersing or dissolving the inorganic filler and the surface treatment agent in a suitable solvent and then removing the solvent, or hydrolyzing the alkoxy groups of the surface treatment agent in an aqueous solution with an acid catalyst to convert them to silanol groups, attaching them to the inorganic filler surface in the aqueous solution, and then removing the water. In any of these methods, the reaction between the inorganic filler surface and the surface treatment agent is completed by heating in the range of 50 to 150°C, and the surface treatment can be performed. The amount of surface treatment is not particularly limited, and for example, 1 to 10 parts by mass of the surface treatment agent can be used per 100 parts by mass of the inorganic filler before treatment.

[0096] The organic-inorganic composite filler used in the present invention is obtained by adding a monomer to the inorganic filler described above in advance, forming a paste, polymerizing the mixture, and pulverizing it. The organic-inorganic composite filler refers to a filler containing an inorganic filler and a polymer of a polymerizable monomer. Examples of the organic-inorganic composite filler include TMPT filler (trimethylolpropane methacrylate and silica filler mixed, polymerized, and then pulverized). The shape of the organic-inorganic composite filler is not particularly limited, and the particle size of the filler can be appropriately selected. The organic-inorganic composite filler may also be used alone or in combination of two or more types. From the viewpoints of the handleability and mechanical strength of the resulting self-adhesive dental composite resin (X) composition, the average particle size of the organic-inorganic composite filler is preferably 0.001 to 50 μm, more preferably 0.001 to 10 μm.

[0097] Examples of organic filler materials include polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, cross-linked polymethyl methacrylate, cross-linked polyethyl methacrylate, polyamide, polyvinyl chloride, polystyrene, chloroprene rubber, nitrile rubber, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-styrene-butadiene copolymer. These may be used alone or in combination. The shape of the organic filler is not particularly limited, and the particle size of the filler can be appropriately selected. From the viewpoint of the handleability and mechanical strength of the resulting self-adhesive dental composite resin (X), the average particle size of the organic filler is preferably 0.001 to 50 μm, and more preferably 0.001 to 10 μm.

[0098] In this specification, the average particle size of the filler can be determined by laser diffraction scattering or electron microscope observation of the particles. Specifically, laser diffraction scattering is convenient for measuring the particle size of particles 0.1 μm or larger, while electron microscope observation is convenient for measuring the particle size of ultrafine particles less than 0.1 μm. The value of 0.1 μm is measured by laser diffraction scattering.

[0099] Specifically, the laser diffraction scattering method can be performed by, for example, measuring on a volume basis using a laser diffraction particle size distribution analyzer (SALD-2300, manufactured by Shimadzu Corporation) and a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium.

[0100] Specifically, electron microscope observation can be performed by taking a photograph of the particles using an electron microscope (S-4000 model, manufactured by Hitachi, Ltd.) and measuring the particle diameters of the particles (200 or more) observed within a unit field of view of the photograph using image analysis particle size distribution measurement software (Mac-View, manufactured by Mountec Co., Ltd.). In this case, the particle diameter is determined as the arithmetic mean value of the longest and shortest lengths of the particles, and the average primary particle diameter is calculated from the number of particles and their particle diameters.

[0101] The self-adhesive dental composite resin (X) of the present invention preferably uses a mixture or combination of two or more fillers with different materials, particle size distributions, and morphologies. Combining two or more fillers allows the fillers to be densely packed and increases the number of interaction points between the fillers and the monomer, or between the fillers themselves. Furthermore, the type of filler makes it possible to control the fluidity of the paste depending on the presence or absence of shear force. In particular, from the viewpoint of the handleability and paste properties of the self-adhesive dental composite resin (X) of the present invention, the filler (d) may be a combination (I) of a filler (di) having an average particle size of 1 nm or more but less than 0.1 μm and a filler (d-ii) having an average particle size of 0.1 μm or more but 1 μm, a combination (II) of a filler (di) having an average particle size of 1 nm or more but less than 0.1 μm and a filler (d-iii) having an average particle size of more than 1 μm but 10 μm, or a combination (III) of a filler (d) having an average particle size of 1 nm or more but less than 0.1 μm and a filler (d-iii) having an average particle size of 1 μm or more but 10 μm, or a combination (IV ... 0.1 μm and a filler (d-iii) having an average particle size of 1 nm or more but 0.1 μm. Combinations (III) of filler (di) less than 0.1 μm with filler (d-ii) having an average particle size of 0.1 μm to 1 μm or filler (d-iii) having an average particle size greater than 1 μm and less than 10 μm, and combinations (IV) of fillers (d-ii) having average particle sizes of 0.1 μm to 1 μm are preferred. Among these combinations, (I), (II), and (III) are more preferred, and (I) and (II) are even more preferred, from the viewpoint of paste properties and cavity sealing. The combination (IV) of fillers (d-ii) having average particle sizes of 0.1 μm to 1 μm refers to an embodiment containing two fillers (d-ii) having different average particle sizes of 0.1 μm to 1 μm. Note that, as long as the combination is as described above, different types of fillers may be included in the fillers (d) having each particle size. Furthermore, particles other than fillers may be unintentionally included as impurities within a range that does not impair the effects of the present invention.

[0102] The content of the filler (d) is not particularly limited, but from the viewpoint of the mechanical strength of the cured product and adhesion to tooth tissue, it is preferably 50 to 90 parts by mass, more preferably 55 to 85 parts by mass, and even more preferably 60 to 80 parts by mass, per 100 parts by mass of the total amount of the self-adhesive dental composite resin (X).

[0103] The method for producing the self-adhesive dental composite resin (X) is not particularly limited as long as it contains the above-mentioned components, the content of the monomer (a) having an acidic group is 1 to 30 parts by mass per 100 parts by mass of the total amount of monomers, and preferably the content of the filler (d) is 50 to 90 parts by mass per 100 parts by mass of the total amount of the self-adhesive dental composite resin (X), and the self-adhesive dental composite resin (X) can be easily produced by a method known to those skilled in the art.

[0104] <Polymerization accelerator (e)> The self-adhesive dental composite resin (X) can use a polymerization accelerator (e) together with a water-soluble photopolymerization initiator (c-1) or a water-insoluble photopolymerization initiator (c-2) and / or a chemical polymerization initiator described below. Examples of the polymerization accelerator (e) used in the present invention include amines, sulfinic acid and its salts, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds.

[0105] Amines used as the polymerization accelerator (e) can be divided into aliphatic amines and aromatic amines. Examples of aliphatic amines include primary aliphatic amines such as n-butylamine, n-hexylamine, and n-octylamine; secondary aliphatic amines such as diisopropylamine, dibutylamine, and N-methylethanolamine; and tertiary aliphatic amines such as N-methyldiethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among these, tertiary aliphatic amines are preferred from the viewpoint of the curing property and storage stability of the self-adhesive dental composite resin (X), and among them, N-methyldiethanolamine and triethanolamine are more preferably used.

[0106] Examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-diisopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, and N,N-diethyl-p -toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, N,N-dimethyl-3,5-di-t-butylaniline, 4-(N,N-dimethylamino)ethyl benzoate, 4-(N,N-dimethylamino)methyl benzoate, 4-(N,N-dimethylamino)propyl benzoate, 4-(N,N-dimethylamino)n-butoxyethyl benzoate, 4-(N,N-dimethylamino)2-(methacryloyloxy)ethyl benzoate, 4-(N,N-dimethylamino)benzophenone, 4-(N,N-dimethylamino)butyl benzoate, and the like. Among these, at least one selected from the group consisting of N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate, and 4-(N,N-dimethylamino)benzophenone is preferably used, from the viewpoint of being able to impart excellent curing properties to the self-adhesive dental composite resin (X).

[0107] Specific examples of sulfinic acids and salts thereof, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds include those described in WO 2008 / 087977.

[0108] The polymerization accelerator (e) may be contained alone or in combination of two or more. The content of the polymerization accelerator (e) used in the present invention is not particularly limited. However, from the viewpoint of the curing property of the resulting self-adhesive dental composite resin (X), the content is preferably 0.001 to 30 parts by mass, more preferably 0.01 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the total amount of monomers in the self-adhesive dental composite resin (X). When the content of the polymerization accelerator (e) is equal to or greater than the lower limit, polymerization proceeds sufficiently, and sufficient bond strength is easily obtained. A content of the polymerization accelerator (e) of 0.05 parts by mass or more is more preferable. On the other hand, when the content of the polymerization accelerator (e) is equal to or less than the upper limit, sufficient adhesiveness is easily obtained and precipitation of the polymerization accelerator (e) itself from the self-adhesive dental composite resin (X) is suppressed. Therefore, a content of 20 parts by mass or less is more preferable.

[0109] <Chemical polymerization initiator> The self-adhesive dental composite resin (X) of the present invention can further contain a chemical polymerization initiator, and an organic peroxide is preferably used. The organic peroxide used as the chemical polymerization initiator is not particularly limited, and known organic peroxides can be used. Representative organic peroxides include, for example, ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates. Specific examples of these organic peroxides include those described in International Publication No. 2008 / 087977. The chemical polymerization initiator may be used alone or in combination of two or more.

[0110] <Fluoride ion-releasing substances> The self-adhesive dental composite resin (X) of the present invention may further contain a fluoride ion-releasing substance. By containing a fluoride ion-releasing substance, a self-adhesive dental composite resin (X) can be obtained that can impart acid resistance to tooth structure. Examples of such fluoride ion-releasing substances include metal fluorides such as sodium fluoride, potassium fluoride, sodium monofluorophosphate, lithium fluoride, and ytterbium fluoride. The above fluoride ion-releasing substances may be contained alone or in combination of two or more.

[0111] The self-adhesive dental composite resin (X) of the present invention may contain known additives within the range that does not impair performance. Examples of such additives include polymerization inhibitors, antioxidants, pigments, dyes, UV absorbers, solvents such as organic solvents, and thickeners. One type of additive may be used alone, or two or more types may be used in combination. In some embodiments, the content of solvents (e.g., water, organic solvents) in the self-adhesive dental composite resin (X) is preferably less than 1% by mass, more preferably less than 0.1% by mass, and even more preferably less than 0.01% by mass, based on the total mass of the self-adhesive dental composite resin (X).

[0112] Examples of the polymerization inhibitor include hydroquinone, hydroquinone monomethyl ether, dibutylhydroquinone, dibutylhydroquinone monomethyl ether, t-butylcatechol, 2-t-butyl-4,6-dimethylphenol, 2,6-di-t-butylphenol, 3,5-di-t-butyl-4-hydroxytoluene, etc. The content of the polymerization inhibitor is preferably 0.001 to 1.0 part by mass per 100 parts by mass of the monomer (a) of the self-adhesive dental composite resin (X).

[0113] Next, the glass ionomer cement (Y) will be described.

[0114] The glass ionomer cement (Y) is a composition containing a fluoroaluminosilicate glass powder (f), a polycarboxylic acid polymer (g), and water (h).

[0115] <Fluoroaluminosilicate glass powder (f)> Fluoroaluminosilicate glass powder (f) can be made of materials that have been used in dental cements, and contains Al as the main component. 3+ , Si 4+ , F-, O 2- Contains Sr 2+ and / or Ca 2+ A fluoroaluminosilicate glass powder containing the following is preferred. The fluorine (F) content in the fluoroaluminosilicate glass powder is preferably 1 to 35 mass%, more preferably 3 to 25 mass%. The aluminum content in the fluoroaluminosilicate glass powder, calculated as aluminum oxide (Al2O3), is preferably 15 to 40 mass%, more preferably 20 to 35 mass%. The silicon content in the fluoroaluminosilicate glass powder, calculated as silicon oxide (SiO2), is preferably 15 to 50 mass%, more preferably 20 to 40 mass%. The phosphorus content in the fluoroaluminosilicate glass powder, calculated as phosphorus (V) oxide (P2O5), is preferably 0 to 15 mass%, more preferably 1 to 7 mass%. The calcium content in the fluoroaluminosilicate glass powder is preferably 0 to 30 mass% and more preferably 1 to 20 mass% in terms of calcium oxide (CaO). The strontium content in the fluoroaluminosilicate glass powder is preferably 0 to 40 mass% and more preferably 10 to 30 mass% in terms of strontium oxide (SrO). The content of the fluoroaluminosilicate glass powder (f) is preferably 25 to 85 parts by mass per 100 parts by mass of the total amount of the glass ionomer cement (Y). When the content of the fluoroaluminosilicate glass powder (f) is equal to or greater than the lower limit, the strength of the set body is improved, and when the content is equal to or less than the upper limit, an increase in viscosity can be suppressed.

[0116] <Polycarboxylic acid polymer (g)> The polycarboxylic acid polymer (g) is not particularly limited, and a homopolymer or copolymer of an α,β-unsaturated carboxylic acid can be used. Examples of α,β-unsaturated carboxylic acids include acrylic acid, methacrylic acid, 2-chloroacrylic acid, 3-chloroacrylic acid, aconitic acid, mesaconic acid, maleic acid, itaconic acid, fumaric acid, glutaconic acid, and citraconic acid. The polycarboxylic acid polymer (g) may also be a copolymer of an α,β-unsaturated carboxylic acid and a monomer copolymerizable with the α,β-unsaturated carboxylic acid. Examples of monomers copolymerizable with the α,β-unsaturated carboxylic acid include acrylamide, acrylonitrile, methacrylic acid esters, acrylates, vinyl chloride, allyl chloride, and vinyl acetate. In this case, the ratio of the α,β-unsaturated carboxylic acid to the monomers constituting the polycarboxylic acid polymer is preferably 50% by mass or more. The polycarboxylic acid polymer is preferably a homopolymer or copolymer of acrylic acid or itaconic acid. At least a part of the polycarboxylic acid polymer may be in the form of powder.

[0117] The weight-average molecular weight of the polycarboxylic acid polymer (g) is preferably in the range of 4,000 to 40,000. A weight-average molecular weight of 4,000 or higher results in excellent strength and durability of the cured product and may even further improve adhesion to tooth tissue. A weight-average molecular weight of 40,000 or less is preferable because it allows for a moderate consistency during mixing and facilitates easy mixing. The weight-average molecular weight refers to the weight-average molecular weight in terms of polystyrene determined by gel permeation chromatography (GPC). Specifically, the following method can be used: Tetrahydrofuran is used as the eluent, and two "TSKgel SuperMultipore HZM-M" columns and one "TSKgel SuperHZ4000" column, both manufactured by Tosoh Corporation, are connected in series. The GPC system used is the "HLC-8320GPC" manufactured by Tosoh Corporation, equipped with a differential refractive index detector (RI detector). For the measurement, 4 mg of sample is dissolved in 5 mL of tetrahydrofuran to prepare a sample solution. Next, the column oven temperature is set to 40°C, and 20 μL of sample solution is injected at an eluent flow rate of 0.35 mL / min to measure the sample chromatogram. Meanwhile, 10 standard polystyrene samples with molecular weights ranging from 400 to 5,000,000 are measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight is created. Based on this calibration curve, the weight-average molecular weight is calculated from the chromatogram of the sample measured as described above.

[0118] <Water(h)> The glass ionomer cement (Y) must contain water (h) for the curing of the polycarboxylic acid polymer (g) and the fluoroaluminosilicate glass (f). The content of water (h) per 100 parts by mass of the glass ionomer cement (Y) is preferably 0.1 to 95 parts by mass, more preferably 0.5 to 90 parts by mass, and even more preferably 1 to 85 parts by mass. In one embodiment, the content of water (h) per 100 parts by mass of the glass ionomer cement (Y) may be 1 to 65 parts by mass.

[0119] <Monomer (i)> In a preferred embodiment, a dental filling kit is provided in which the glass ionomer cement (Y) further comprises a monomer (i) from the viewpoints of adhesion to the self-adhesive dental composite resin (X) and toughness of the glass ionomer cement (Y). A radical monomer is preferably used as the monomer (i). Specific examples of the radical monomer in the monomer (i) include (meth)acrylate-based monomers, (meth)acrylamide-based monomers, esters of α-cyanoacrylic acid, (meth)acrylic acid, α-halogenated acrylic acid, crotonic acid, cinnamic acid, sorbic acid, maleic acid, itaconic acid, etc., vinyl esters, vinyl ethers, mono-N-vinyl derivatives, styrene derivatives, etc. Among these, (meth)acrylate-based monomers and (meth)acrylamide-based monomers are preferred from the viewpoint of curability. Specific examples of the monomer (i) contained in the glass ionomer cement (Y) include monomers similar to those contained in the self-adhesive dental composite resin (X) (monomer (a) having an acidic group, monomer (b) not having an acidic group), and one type may be used alone, or two or more types may be used in combination.

[0120] <Photopolymerization initiator (j)> In another preferred embodiment, from the viewpoint of adhesion to the self-adhesive dental composite resin (X) and the strength of the glass ionomer cement (Y), a dental filling kit is provided in which the glass ionomer cement (Y) further contains a monomer (i) and a photopolymerization initiator (j). Specific examples of the photopolymerization initiator (j) include those similar to the photopolymerization initiator (c) contained in the self-adhesive dental composite resin (X), and one type may be used alone, or two or more types may be used in combination.

[0121] <Configuration of the dental filling kit of the present invention> The dental filling kit of the present invention includes a self-adhesive dental composite resin (X) and a glass ionomer cement (Y), which are typically filled in separate containers. The self-adhesive dental composite resin (X) may be a one-component or two-component type, but a one-component type is preferred from the standpoints of ease of use and hardening time. The glass ionomer cement (Y) may be a two-component type consisting of two materials, a powder material and a liquid material, or a two-component type consisting of two types of paste, but a two-component type consisting of two types of paste is preferred from the standpoint of ease of use.

[0122] The dental filling kit of the present invention may further be combined with an etching material (C), a dental primer (D), a dental bonding material (E), etc. From the viewpoint of cavity sealing ability, it is preferable to apply the etching material (C) only to the enamel. From the viewpoint of adhesive strength to the tooth structure and cavity sealing ability, it is preferable to combine the dental primer (D) and the dental bonding material (E), and more preferably to combine the dental bonding material (E). The dental primer (D) and the dental bonding material (E) may or may not be polymerized independently, but from the viewpoint of cavity sealing ability, it is preferable to polymerize them by photopolymerization or chemical polymerization. The etching material (C), dental primer (D), and dental bonding material (E) may each be used alone or in combination of two or more. From the viewpoint of cavity sealing ability, the procedure of applying the dental primer (D) after using the etching material (C) and then applying the dental bonding material (E) is preferable. Also, for example, two types of bonding materials may be used, with one dental bonding material being applied first, followed by the other dental bonding material.

[0123] The dental filling kit of the present invention may further contain a conditioner. A known conditioner may be used, and may be applied to the tooth structure before applying the glass ionomer cement (Y). From the viewpoint of ease of use, it is preferable not to use a conditioner.

[0124] <Specific application methods and procedures>

[0125] ·Application of self-adhesive dental composite resin (X) After forming a cavity in the tooth, a self-adhesive dental composite resin (X) is applied. The self-adhesive dental composite resin (X) may be filled from the bottom to partway through the cavity, as shown in Figure 1. The glass ionomer cement 4 is then filled on top of the filled self-adhesive dental composite resin 3. Alternatively, as shown in Figure 2, the entire cavity may be filled to seal it. The glass ionomer cement 4 is then filled on top of the self-adhesive dental composite resin 3 used for sealing. In either case, it is preferable that the area of ​​the self-adhesive dental composite resin 3 in contact with the dentin 1 is larger than that of the glass ionomer cement 4. In the case of a self-adhesive dental composite resin (X) containing a photopolymerization initiator (c), it is cured by irradiation with light using a dental light curing device. In the case of a self-adhesive dental composite resin (X) containing a chemical polymerization initiator, it is left to stand until curing is complete. Thereafter, the surface is subjected to shape correction and polishing in some cases.

[0126] When combined with etching material (C), dental primer (D), dental bonding material (E), etc., use before applying self-adhesive dental composite resin (X).

[0127] ·Application of glass ionomer cement (Y) Glass ionomer cement (Y) is applied to the surface on which self-adhesive dental composite resin (X) has been applied, and in some cases to the tooth structure. Since it is a two-part type, the two are mixed and kneaded before application. After application, if the glass ionomer cement (Y) contains photopolymerization initiator (j), it is irradiated with light using a dental light irradiator to harden it. If it does not contain photopolymerization initiator (j), it is left to stand until hardening is complete. After that, the surface shape is corrected and polished as needed.

[0128] In the present invention, a self-adhesive dental composite resin (X) is used to directly apply to a tooth structure after cavity formation to seal the entire cavity or a portion thereof, and the surface to which the self-adhesive dental composite resin (X) is applied is further coated with a glass ionomer cement (Y), thereby achieving excellent cavity sealing properties while also providing ion release properties. Therefore, another embodiment of the present invention is a dental filling kit in which the self-adhesive dental composite resin (X) is used for direct sealing of the entire cavity or a portion thereof, and the glass ionomer cement (Y) is used for coating the surface to which the self-adhesive dental composite resin (X) is applied.

[0129] Another embodiment of the present invention is a method for restoring teeth, comprising the steps of applying a self-adhesive dental composite resin (X) to a predetermined area of ​​a tooth and applying a glass ionomer cement (Y) to the predetermined area to which the self-adhesive dental composite resin (X) has been applied, wherein the self-adhesive dental composite resin (X) comprises a monomer (a) having an acidic group, a monomer (b) not having an acidic group, and a photopolymerization initiator (c), and the glass ionomer cement (Y) comprises a fluoroaluminosilicate glass powder (f), a polycarboxylic acid polymer (g), and water (h). Each step is as described above in the specific application method and procedure. [Example]

[0130] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples, parts are by mass unless otherwise specified.

[0131] Next, the components of the dental filling kits of the Examples and Comparative Examples are listed below together with their abbreviations.

[0132] Self-adhesive dental composite resin (X) [Monomer (a) having an acidic group] MDP: 10-methacryloyloxydecyl dihydrogen phosphate P-2M: Bis(2-methacryloyloxyethyl) hydrogen phosphate

[0133] [Monomer (b) having no acidic group] Bis-GMA: 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane Bis-MEPP: isopropylidenebis[(4,1-phenylene)oxyethylene] bismethacrylate UDMA: Di-2-methacryloyloxyethyl-2,2,4-trimethylhexamethylene dicarbamate D-2.6E: 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (average number of moles of ethoxy groups added: 2.6) 3G: Triethylene glycol dimethacrylate DD: 1,10-decanediol dimethacrylate MAEA: N-methacryloyloxyethyl acrylamide DEAA: N,N-diethylacrylamide HEMA: 2-hydroxyethyl (meth)acrylate

[0134] [Photopolymerization initiator (c)] Water-soluble photopolymerization initiator (c-1) Li-TPO: Phenyl(2,4,6-trimethylbenzoyl)phosphinic acid lithium salt Non-water-soluble photopolymerization initiator (c-2) CQ: Camphorquinone BAPO: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide TMDPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide

[0135] Filler (d) Filler 1: Nippon Aerosil Co., Ltd., ultrafine silica particle "Aerosil (registered trademark) R 972", average particle size: 16 nm Filler 2: Silane-treated silica 100 g of OX50 (Nippon Aerosil Co., Ltd., ultrafine silica particle "Aerosil (registered trademark) OX50", average particle size: 0.04 μm), 7 g of γ-methacryloyloxypropyltrimethoxysilane, and 200 mL of 0.3 mass% acetic acid aqueous solution were placed in a three-necked flask and stirred at room temperature for 2 hours. After removing water by freeze-drying, the mixture was heated at 80°C for 5 hours to obtain Filler 2. Filler 3: Silane-treated silica powder Silica powder (manufactured by Nichitsu Corporation, product name: Hi-Silica) was pulverized in a ball mill to obtain pulverized silica powder. The average particle size of the obtained pulverized silica powder was measured on a volume basis using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, model "SALD-2300") and found to be 2.2 μm. 100 parts by mass of this pulverized silica powder was surface-treated with 4 parts by mass of γ-methacryloyloxypropyltrimethoxysilane by a conventional method to obtain silane-treated silica powder. Filler 4: Silane-treated barium glass powder Barium glass (manufactured by Estec Co., Ltd., product name "E-3000") was pulverized in a ball mill to obtain barium glass powder. The average particle size of the obtained barium glass powder was measured on a volume basis using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, model "SALD-2300") and was found to be 2.4 μm. 100 parts by mass of this barium glass powder was surface-treated with 3 parts by mass of γ-methacryloyloxypropyltrimethoxysilane by a conventional method to obtain silane-treated barium glass powder. Filler 5: Silane-treated barium glass powder 100 g of GM27884 NF180 grade (barium glass manufactured by SCHOTT, average particle size: 0.18 μm), 13 g of γ-methacryloyloxypropyltrimethoxysilane, and 200 mL of 0.3 mass% acetic acid aqueous solution were placed in a three-necked flask and stirred at room temperature for 2 hours. After removing water by freeze-drying, the mixture was heated at 80°C for 5 hours to obtain Filler 5. Filler 6: Silane-treated barium glass powder 100 g of 8235 UF0.7 grade (barium glass manufactured by SCHOTT, average particle size: 0.7 μm), 6 g of γ-methacryloyloxypropyltrimethoxysilane, and 200 mL of 0.3 mass% acetic acid aqueous solution were placed in a three-necked flask and stirred at room temperature for 2 hours. After removing water by freeze-drying, the mixture was heated at 80°C for 5 hours to obtain Filler 6. Filler 7: Silane-treated spherical silica-titania composite oxide powder 100 g of spherical silica-titania composite oxide (average particle size: 0.3 μm), 10 g of γ-methacryloyloxypropyltrimethoxysilane, and 200 mL of 0.3 mass% acetic acid aqueous solution were placed in a three-necked flask and stirred at room temperature for 2 hours. After removing water by freeze-drying, the mixture was heated at 80°C for 5 hours to obtain Filler 7. Silica powder: Aerosil R812 (manufactured by Nippon Aerosil Co., Ltd.) Strontium glass powder: SiO2 (55 mass%), Al2O3 (10 mass%), SrO (20 mass%), and BO3 (15 mass%) were thoroughly mixed to obtain a raw material composition. Next, the raw material composition was held at 1200°C for 5 hours using a high-temperature electric furnace, melted, and then cooled to obtain strontium glass. Next, the strontium glass was pulverized using a ball mill for 10 hours and then passed through a 200 mesh (ASTM) sieve to obtain strontium glass powder. Barium glass powder: SiO2 (55% by mass), Al2O3 (10% by mass), BaO (30% by mass), and BO3 (10% by mass) were thoroughly mixed to obtain a raw material composition. Next, the raw material composition was held at 1200°C for 5 hours using a high-temperature electric furnace, melted, and then cooled to obtain barium glass. Next, the barium glass was pulverized for 10 hours using a ball mill, and then passed through a 200 mesh (ASTM) sieve to obtain barium glass powder.

[0136] [Polymerization accelerator (e)] DABE: Ethyl 4-(N,N-dimethylamino)benzoate

[0137] [Polymerization inhibitor] BHT: 3,5-di-t-butyl-4-hydroxytoluene

[0138] Glass ionomer cement (Y) [Fluoroaluminosilicate glass powder (f)] Aluminum oxide (21% by mass), silicic anhydride (44% by mass), calcium fluoride (12% by mass), calcium phosphate (14% by mass), and strontium carbonate (9% by mass) were thoroughly mixed to obtain a raw material composition. The raw material composition was then heated to 1200°C for 5 hours in a high-temperature electric furnace, melted, and then cooled to obtain fluoroaluminosilicate glass. The fluoroaluminosilicate glass was then pulverized in a ball mill for 10 hours and passed through a 200-mesh (ASTM) sieve to obtain a fluoroaluminosilicate glass powder.

[0139] [Polyacrylic acid polymer (g)] Polyacrylic acid powder (weight average molecular weight: 25,000, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in water to obtain a 50% by mass aqueous solution of polyacrylic acid.

[0140] [Examples 1 to 20 and Comparative Examples 1 to 5] [Preparation of self-adhesive dental composite resin (X)] The raw materials shown in Tables 1 to 3 were mixed and kneaded in a dark place at room temperature (23°C) to prepare paste-like self-adhesive dental composite resins, and their properties were investigated according to the methods of the following Test Examples 1 to 3. The results are shown in Tables 1 to 4.

[0141] [Mixing Glass Ionomer Cement (Y)] Fluoroaluminosilicate glass powder and an aqueous solution of polyacrylic acid were mixed at a powder-liquid ratio (powder / liquid) of 1.8 to obtain a glass ionomer cement mixture.

[0142] Test Example 1: Bond strength when self-adhesive dental composite resin and glass ionomer cement are laminated together [Shear adhesion test to dentin] The labial surfaces of bovine mandibular anterior teeth were polished under running water with #80 silicon carbide paper (Nihon Kenshi Co., Ltd.) to expose the flat surface of the dentin. The sample teeth were fixed onto tape attached to the bottom of a 15-hole mold (Ultradent, φ35 mm x H25 mm). Plaster was filled into the mold and allowed to stand for approximately 30 minutes to harden. The samples were removed from the mold and polished under running water with #600 silicon carbide paper (Nihon Kenshi Co., Ltd.) to a size sufficient for adhesion (φ2.38 mm or larger). The adhesion surface was then ultrasonically rinsed for 5 minutes.

[0143] A separately prepared 2.38 mm diameter CR filling mold (Bonding Mold Insert, Ultradent) was attached to a dedicated tool (Bonding Clamp, Ultradent). Next, the CR filling mold attached to the dedicated tool was lowered so that it was in close contact with the bonding surface of the sample, and the sample was fixed in place. Next, the dental composite resin prepared in each Example and Comparative Example was thinly filled into the hole of the CR filling mold to a thickness of 1 mm or less. After leaving it for 10 seconds, the self-adhesive dental composite resin was cured by irradiating it with light for 10 seconds using a dental LED light irradiator (Ultradent, product name "VALO") . Glass ionomer cement was then filled into the mold (approximately 2 / 3 of the mold, a total thickness of approximately 2 mm) and stored for 10 minutes at 37°C and 95% RH to cure the glass ionomer cement. The sample was removed from the mold and used as a test sample for adhesion testing. Next, the adhesion test sample was immersed in distilled water in a sample container and left in an incubator set at 37°C for 24 hours, then removed and the adhesive strength was measured. The adhesive strength (shear adhesive strength) was measured by attaching the adhesion test sample to a dedicated holder (Test Base Clamp, Ultradent) and using a dedicated jig (Crosshead Assembly, Ultradent) and a universal testing machine (Shimadzu Corporation) at a crosshead speed of 1 mm / min, and the average values ​​are shown in the table (n=10).

[0144] Test Example 2: Cavity sealing The surfaces of bovine teeth were polished under running water with #80 silicon carbide paper (manufactured by Nihon Kenshi Co., Ltd.) to expose the flat surface of the enamel. A cylindrical cavity measuring 4 mm in diameter and 2 mm deep was formed using a Mani Diabur SF-21 (manufactured by Mani Co., Ltd.) with an air turbine under running water. After formation, the cavity was rinsed with running water and then dried with an air blower. Pattern 1: Self-adhesive dental composite resin was filled to a depth of less than 1 mm to seal the cavity, left for 10 seconds, and then irradiated with a dental LED light irradiator (Ultradent, product name "VALO") for 10 seconds. Glass ionomer cement was then filled and stored for 10 minutes in an environment of 37°C and 95% RH to harden the glass ionomer cement, resulting in a test sample. Pattern 2: Glass ionomer cement was filled to a depth of less than 1 mm to seal the cavity, and then stored for 10 minutes at 37°C and 95% RH to harden. Next, a self-adhesive dental composite resin was filled in, and the cavity was irradiated for 10 seconds with a dental LED light irradiator (Ultradent, product name "VALO") to prepare a test sample.

[0145] For both patterns 1 and 2, samples were observed using optical coherence tomography (OCT, IVS-2000, Santec Corporation) to evaluate cavity compatibility (n=3). Samples with no cavity delamination were scored 0, samples with at least one cavity side delamination were scored 1, samples with at least one cavity floor delamination were scored 2, and samples with at least one cavity side and cavity floor delamination were scored 3.

[0146] Test Example 3: Fluoride ion release simulating a real cavity A 20 mm diameter, 2 mm thick mold was filled with approximately 1 mm of self-adhesive dental composite resin and irradiated from above with a dental LED light source (Ultradent, product name "VALO") for 10 seconds, for a total of nine points to ensure the entire filling was illuminated. Glass ionomer cement was then filled into the remaining portion of the mold and stored at 37°C and 95% RH for 10 minutes to cure. The sides and bottom of the cured material, excluding the top surface, were covered with nail polish to simulate a cavity. The material was then immersed in 10 ml of phosphate buffer (pH 7, 37°C). Fluoride ions released into the phosphate buffer were quantified using a fluoride ion electrode (LAQUA PH / ION METER F-73, Horiba, Ltd.) after 28 days of immersion, and the average fluoride ion release (μg / g) per gram of cured material was calculated (n=3). In the comparative example, after the glass ionomer cement was hardened, it was filled with a self-adhesive dental composite resin, and the sides and bottom surfaces of the hardened product, except for the top surface, were covered with nail polish to simulate a cavity.

[0147] [Table 1]

[0148] [Table 2]

[0149] [Table 3]

[0150] [Table 4] (In the table, when the material on the cavity bottom side is "Example 1," this means that the self-adhesive dental composite resin of Example 1 was applied to the cavity bottom side.)

[0151] The results in Tables 1 and 2 show that the dental filling kits of Examples 1 to 19 had bond strengths to dentin of 7 MPa or more and cavity sealing scores of 1 or less. On the other hand, as shown in Table 3, Comparative Examples 1 to 4 showed good cavity sealing performance with a score of 1 in Pattern 2, but all received a score of 2 in Pattern 1. Furthermore, Comparative Examples 1 to 4 had low bond strengths to dentin of 5 MPa or less. Comparative Examples 1 and 3 correspond to Examples 1 and 4 of Patent Document 5, respectively, confirming the advantageous effects of the present invention over the prior art. As shown in Table 4, in Example 20, a method in which the cavity floor was filled with a self-adhesive dental composite resin and the cavity surface was filled with glass ionomer cement resulted in a high amount of fluoride release, whereas in Comparative Example 5, almost no fluoride was released. [Industrial Applicability]

[0152] The dental filling kit of the present invention can be suitably used for filling treatment in dental treatment, and is particularly suitable for filling treatment of cavities of 2 mm or more. [Explanation of symbols]

[0153] 1: Dentin 2: Enamel 3: Self-adhesive dental composite resin 4: Glass ionomer cement

Claims

1. A self-adhesive dental composite resin (X) containing a monomer (a) having an acidic group, a monomer (b) not having an acidic group, and a photopolymerization initiator (c); a glass ionomer cement (Y) containing a fluoroaluminosilicate glass powder (f), a polycarboxylic acid polymer (g), and water (h); A dental filling kit, wherein the content of the monomer (a) having an acidic group is 1 to 30 parts by mass per 100 parts by mass of the total amount of the monomers of the self-adhesive dental composite resin (X).

2. The dental filling kit according to claim 1, wherein the self-adhesive dental composite resin (X) further comprises a filler (d), and the content of the filler (d) is 50 to 90 parts by mass in a total amount of 100 parts by mass of the self-adhesive dental composite resin (X).

3. The dental filling kit of claim 2, wherein the filler (d) comprises a filler (d-ii) having an average particle size of 0.1 μm or more and 1 μm or less and / or a filler (d-iii) having an average particle size of more than 1 μm and 10 μm or less.

4. The dental filling kit according to claim 3, wherein the filler (d-ii) and / or the filler (d-iii) comprises an inorganic filler containing silicon atoms and / or an inorganic filler composed of an oxide of silicon atoms, the inorganic filler has hydroxyl groups on its surface, and the hydroxyl groups are surface-treated with a surface treatment agent.

5. The dental filling kit according to any one of claims 2 to 4, wherein the filler (d) is selected from the group consisting of a combination (I) of a filler (d-i) having an average particle size of 1 nm or more and less than 0.1 μm and a filler (d-ii) having an average particle size of 0.1 μm or more and 1 μm or less, a combination (II) of a filler (d-i) having an average particle size of 1 nm or more and less than 0.1 μm and a filler (d-iii) having an average particle size of more than 1 μm and 10 μm or less, a combination (III) of a filler (d-i) having an average particle size of 0.1 μm or more and 1 μm or less, and a filler (d-iii) having an average particle size of more than 1 μm and 10 μm or less, and a combination (IV) of fillers (d-ii) having an average particle size of 0.1 μm or more and 1 μm or less.

6. The dental filling kit according to any one of claims 1 to 5, wherein the glass ionomer cement (Y) further comprises a monomer (i) and a photopolymerization initiator (j).

7. The dental filling kit according to any one of claims 1 to 6, wherein the self-adhesive dental composite resin (X) is of one-component type.

8. The dental filling kit according to any one of claims 1 to 7, wherein the content of the fluoroaluminosilicate glass powder (f) is 25 to 85 parts by mass per 100 parts by mass of the total amount of the glass ionomer cement (Y).

9. A dental filling kit according to any one of claims 1 to 8, wherein the self-adhesive dental composite resin (X) is for direct sealing of the entire or part of a cavity, and the glass ionomer cement (Y) is for covering the surface to which the self-adhesive dental composite resin (X) is applied.

Citation Information

Patent Citations

  • self-adhesive dental material

    JP2004529946A

  • Dental composite resin and dental packing kit

    JP2006131621A

  • Powder liquid-type dental resin-enriched glass ionomer cement

    JP2014181190A

  • Self-adhesive dental composite resin

    JP2017105716A

  • Dental adhesive composition

    JP2018065831A